Diseño de Política Pública vinculante a los emprendimientos Microempresariales con enfoque de desarrollo económico Territorial para la sostenibilidad de los sistemas Productivos locales de la provincia de San Martín - Rengifo Isuiza, Juan Losber (2014)
Currently in the province of San Martin, as well as the major cities of the region and the country has a great entrepreneurial mass, this in part as a result of the need to generate income to support the family and others in a lower percentage as a result of the dynamism seize opportunities that are being created in the local markets. Public policy aimed at strengthening business through its competent institutions in the province of San Martin, is not being efficient in achieving its objectives; the investigative process demonstrates a low level of awareness of decision makers about their competence and strategic productive sectors in your jurisdiction. The actions of public organizations promoting MSEs do not involve the entrepreneurial process of investigation, limiting their capacity and timely development in local production systems. The research has the general objective: To identify the factors that generate limited linkage of public policies of entrepreneurship, to propose a binding public policy with a focus on Territorial Economic Development that contributes to the stability of the micro - business sector in the province of San Martín. Entrepreneurs districts Tarapoto (239), Morales (56) and Shilcayo (56), as a representative sample: To which descriptive research on a mixed (quantitative and qualitative) approach, identifying as units of analysis raised a total of 7264 reported by the SUNAT microentrepreneurs through 2013; and, 6 private public organizations promoting MYPES. Determining as sources: Entrepreneurs and owners of the 351 micro-enterprises in the selected representatives of the sponsoring organizations of MYPES districts and their management tools. According to the results of the research process factors that generate limited linking public to entrepreneurship policies are identified: (a) The weak political decision relationship - entrepreneurial process based on the low level of technocratic political leadership and poor prioritization of targets for entrepreneurial development in the public agenda. (b) The limited participation of entrepreneurial actors in the process of implementation of public actions to strengthen the business.; (c) The low level of political will to support entrepreneurial development. Depending on the results of the research model binding public policy based on knowledge of the theories Polanyi, Senge proposes, and Hessel; the theory of political leadership Natera; and focus of citizen participation Dilla. The model poses as a binding condition of the existence of a legitimate public action based on the basis of a real participation of entrepreneurial actors in the processes of design actions to strengthen the entrepreneurial process. The application of the model will help transcend situational problem.